Rise of 'lonely' consumers in the post-COVID-19 era : a synthesised review on psychological, commercial and social implications - Wang, Xueqin (2021)
Loneliness is a pervasive problem recognised as a serious social issue, and the prevailing COVID-19 pandemic has exacerbated loneliness to greater prominence and concern. We expect a rise of a massive group of 'lonely' consumers who are deeply entrenched in the social isolation caused by COVID-19. There is an urgent need to revisit the phenomenon of lonely consumers to better prepare academic researchers, public policy makers and commercial managers in the post-COVID-19 era. Thus, this study conducts a synthesised review on past studies of lonely consumers. Based on an inductive analysis of 56 articles, 74 key themes are identified. These key themes are further categorised into five major clusters by way of a co-occurrence network analysis. Respectively, the five clusters address the psychological implications related to the dynamics between nonhuman attachment and consumers' loneliness, the commercial implications related to the paradoxical motivations of affiliation and self-affirmation in product selection and the dual information processing mechanism in response to advertisement appeals, and the social implications related to consumers' well-being in an ageing society and the anthropomorphic companionship in a virtual world. A list of research questions is proposed that concludes the review study.